Penerapan Balanced Scorecard (BSC) Dalam Pengukuran Kinerja Organisasi Publik (Studi Kasus pada Dinas Perhubungan Kota Malang) - Sukma Asri Fitria; Ronny Malavia Mardani; Tri Sugiarti Ramadhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract Public organizations are required to demonstrate effective, efficient, and accountable performance in response to increasing public demands for service quality. One comprehensive approach to measuring organizational performance is the Balanced Scorecard (BSC), which integrates four perspectives: financial, customer, internal business process, and learning and growth. This study aims to analyze the implementation of the Balanced Scorecard in measuring the performance of public organizations at the Department of Transportation of Malang City. The research employs a descriptive quantitative approach using a case study method, with a population of 138 civil servants and a sample of 103 respondents. The data consist of primary data collected through employee self-assessment questionnaires and secondary data obtained from financial reports and institutional documents. Data analysis techniques include descriptive statistics and narrative analysis. The results indicate that the performance of the Department of Transportation of Malang City based on the four BSC perspectives is generally categorized as good. The financial perspective reflects relatively economical budget management, while the customer, internal business process, and learning and growth perspectives support the implementation of public services. Overall, the Balanced Scorecard provides a comprehensive overview of organizational performance in the public sector. Keywords: Balanced Scorecard; Public Organizational Performance; Performance Measurement; Department of Transportation.